Towards the decriminalisation of attempted suicide in Kenya: diversion as a restorative justice mechanisms - Hamada, A. A. S. (Strathmore University, 2025)
The Centre for Disease Control (CDC) defines attempted suicide as an attempt where someone harms themselves with any intent to end their life, but they do not die as a result of this action.1 According to the World Health Organization (WHO), 703,000 people die each year as a result of suicide and of these cases, there are even more of those who attempt suicide being projected at least 20 times more frequent than “completed suicides”.2 In 2019, the WHO age-standardised report estimated that Africa carried the highest suicide burden at 11.2 per 100, 000 population while the suicide rate in Kenya was estimated at 11.0 per 100, 000 population.3 Research suggests that psychiatric illness play a major role in attempted suicide with depression and other mental disorders emerging as significant risk factors for both the youth and adults.4 The impact of childhood adversities, including experiences such as sexual or physical abuse, along with substance abuse, stressful life events (such as bereavement, job loss, or relationship breakdown), financial struggles, impending legal issues, and facing or being recently diagnosed with a terminal illness are leading causes for attempted suicide.5 Quantitative studies highlight additional risk factors, such as sociodemographic elements (male gender for completed suicides and female gender for non-fatal suicidal behaviour), younger age, genetic predisposition, and personality traits like neuroticism as contributing factors too.6 Socioeconomic status also plays a role, with low status correlating with increased suicide risk. 7Qualitative research in specific regions further identifies poverty, intimate partner violence, family rejection, social isolation, stigma, and chronic physical illness as contributing factors to suicidal behaviour.8 This complexity suggests a multifaceted interplay of factors, often interacting or modifying each other, contributing to the understanding of the causes behind both suicide and attempted suicide
Full - text undergraduate research project